2020
DOI: 10.1016/j.conbuildmat.2020.119945
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the slump and strength development of geopolymer concrete

Abstract: Cement production is estimated to be responsible for 5-8% of global total carbon dioxide (CO2) emissions. Geopolymer concrete (GC) is claimed to release up to 45% less CO2 for a comparable concrete, but is more difficult to manufacture. This study investigated the effect of factors other than mix design on the slump and strength development of GC produced from low-calcium fly ash (FA) and up to 50% ground granulated blastfurnace slag (GGBS) replacement; these were: curing methods and temperatures (at 10, 20 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 65 publications
1
23
0
1
Order By: Relevance
“…According to Nguyen et al [ 2 ], increasing water/solid ratio from 0.2 to 0.3, can decrease the compressive strength of the FA-based GPC for alkaline-to-binder ratios of 0.3 and 0.4, while tests by Ahmad [ 59 ] for GPC subjected to initial curing at 70 °C (Oven) for 24 h showed that the optimum water/binder ratio is 0.25 to obtain maximum compressive strength. There was a strength increase with increasing alkali/fly ash ratio up to 0.45, lower than 0.5 measured by Al Bakri et al [ 60 ] and Abdullah et al [ 50 ].…”
Section: State-of-the-art Review Of Mechanical Properties Of Geopolymer Concretementioning
confidence: 99%
See 2 more Smart Citations
“…According to Nguyen et al [ 2 ], increasing water/solid ratio from 0.2 to 0.3, can decrease the compressive strength of the FA-based GPC for alkaline-to-binder ratios of 0.3 and 0.4, while tests by Ahmad [ 59 ] for GPC subjected to initial curing at 70 °C (Oven) for 24 h showed that the optimum water/binder ratio is 0.25 to obtain maximum compressive strength. There was a strength increase with increasing alkali/fly ash ratio up to 0.45, lower than 0.5 measured by Al Bakri et al [ 60 ] and Abdullah et al [ 50 ].…”
Section: State-of-the-art Review Of Mechanical Properties Of Geopolymer Concretementioning
confidence: 99%
“…The superiority of slag on fly ash for GPC subjected to different curing regimes was also observed by Kurtoğlu et al [ 78 ]. Other tests showed that replacement of fly ash by GGBS up to 30% leads to an increase in compressive strength regardless of the curing temperature [ 2 ]. On the other hand, Yunsheng et al [ 27 ] and Abhilash et al [ 79 ] reported that the maximum compressive strength is related to replacing 50% metakaolin with GGBS.…”
Section: State-of-the-art Review Of Mechanical Properties Of Geopolymer Concretementioning
confidence: 99%
See 1 more Smart Citation
“…Many factors that affect the compressive strength, flexural strength and other mechanical properties of geopolymers have been reported by different researchers [ 22 , 38 , 39 , 40 , 41 , 42 ]. These factor, such as different calcium-containing raw materials [ 21 , 43 ], ionic additives, curing procedures and post-curing chemical treatment, have been considered important for final properties [ 44 , 45 , 46 ]. An amorphous structure of geopolymers is better for realizing anticipated mechanical strength.…”
Section: Geopolymersmentioning
confidence: 99%
“…Setelah proses pencampuran beton selesai, maka diperlukan pengujian beton segar. Pengujian beton segar dilakukan untuk mengetahui kekentalan beton yang berpengaruh terhadap kemudahan pengerjaan (workability) dan homogenitas dari campuran beton (Nguyen et al, 2020). Pada penelitian ini dilakukan pengujian beton segar dengan slump test.…”
Section: Pengujian Beton Segarunclassified